Under the Disguise of Participation: Community Forestry as a New Form of Land Rush in Liberia - Rösch, Ricarda (The Transnational Land Rush in Africa, 2021)
A variety of national and international actors embarked upon the reform of the Liberian forest sector after the end of the civil war in 2003, in part due to the logging sanctions enacted by the United Nations during the conflict. One result of these reform efforts was the adoption of the Community Rights Law with Respect to Forest Lands in 2009. The law introduces community forestry and is considered to be one of the most progressive laws on the African continent. Yet, fieldwork in Liberia conducted between October 2017 and January 2018 and between February and March 2018 indicates that the community forestry regime is redefined and undermined by different actors, and, in practice, contributes to land grabbing. After providing a brief overview of the government’s post-war Foreign Direct Investment (FDI) strategy, this chapter explores: (1) the reform of the logging sector after the war (2) the legal framework of community forestry, and (3) the implementation of community forestry based upon two case studies.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Community forestry; Customary land rights